A fault-tolerant control strategy for switched reluctance motor drive for electric vehicles under short-fault condition. (September 2018) - Ma, Mingyao; Wang, Rui; Li, Fei; Wang, Jianing; Yang, Shuying
Abstract: This paper proposed a new fault-tolerant control strategy for the short-fault occurring in the switched reluctance motor (SRM) electric drive system, which can not only suppress severe torque ripples in short faults, but also can adjust the total torque and torque ripples in different working conditions to ensure the reliability of the SRM system and the safety of drivers. The proposed strategy is to select the derating states according to the operation requirements when switches short faults occur, then shorten the conduction angle of the faulty phase and adjust the duty cycle of all switches of three phases according to the proposed fault-tolerance rule. Furthermore, the fault-tolerant strategy was applied to a three-phase 12/8 SRM drive. Simulation results in MATLAB/Simulink and experiments on the RT-LAB validate the effectiveness of the proposed strategy, which may be significant in reliability of electric vehicles. Highlights: A fault-tolerant control strategy for SRM under short-fault condition is proposed. In fault-tolerant control, three phase reference currents should be recalculated. In fault-tolerant control, the duty cycles of the power switches should be adjusted. The method effectively suppresses the fault torque ripples of SRM system. Fault-tolerant control method can effectively improve the reliability of SRM system.